(untitled) (Journal of Engineering Science, 2022)
Workers’ performance and efficiency are dependent on their workplace facilities. The present study attempts to identify the six physical factors of the workplace environment: furniture and equipment design, air quality, temperature, sanitation, lighting and noise. Workers’ feedback is evaluated by using 5 scale Likert method and it is found that found workplace temperature is most critical for workers’ performance. The purpose of this study is to identify workers’ impressions about their workplace environment and provide a better understanding to the managers about improvement. Industry-level emphasis on these factors can improve workers’ performance standards and production quality. Previous work performance studies are not focused on hygiene and sanitation facility but due to the corona pandemic situation sanitation concern has been raised. This study aims to explore the relationship of these factors with gender and work experience of the workers. Variation in each group has provided an understanding of the basic demand of each type of worker. Journal of Engineering Science 12(3), 2021, 57-66